If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -12 = -12 + 4y Reorder the terms: -12 + 4y = -12 + 4y Add '12' to each side of the equation. -12 + 12 + 4y = -12 + 12 + 4y Combine like terms: -12 + 12 = 0 0 + 4y = -12 + 12 + 4y 4y = -12 + 12 + 4y Combine like terms: -12 + 12 = 0 4y = 0 + 4y 4y = 4y Add '-4y' to each side of the equation. 4y + -4y = 4y + -4y Combine like terms: 4y + -4y = 0 0 = 4y + -4y Combine like terms: 4y + -4y = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 7-5(5a-4)=6-4a | | -6k-7k= | | 10-a=12 | | 14x(2)+5-[7(x(2)+-2)+4]= | | 21x^2+12x-1= | | 5(x-7)+2=4 | | 1/2(x-3)+(3/2-x)=5x | | 5x+2y=-9 | | 7n+1.3=22.3whatisn | | 19-3n=5n-13 | | 36+62= | | 3c-11=7c+19 | | 3-7x-x=-1 | | 6(1+6b)minus-8=106 | | -5x+12=6 | | -11-5a=6(5a+14) | | 8(3x+5)-(7x-2)=8 | | -3-6x=-5-4x | | 6(1+6b)-8=106 | | 2r=8r-30 | | 8-3a=2 | | 3r+2=3r+2 | | 3x-30y=-6 | | -11-2v=5-6v | | 2b-7=19 | | 14-b=2b-7 | | 2(3x-4)=10x-20 | | 45-5a=-10a | | (5x^2+6x)(20x^2-11x-3)=0 | | 5(6-4n)=n+21 | | 28+28m=-5(3m+2) | | -5n+8=-6n+1 |